Informatics - Editor, Editor (Journal of Engineering Education Transformations, 2006)
News: * News from Engineering Education Foundation .... * IE (I) News. Views: * Narayan Murthy stresses on engineering education reforms. * Prof. P.K. Ahluwalia, Director, UIIT and Chairman, Physics Department.